THE ROLE OF THE FAMILY ENVIRONMENT IN CHILD DEVELOPMENT AT AL IZZAH KINDEGARTEN, PURI DISTRICT, MOJOKERTO REGENCY - Lida Khalimatus Sadiyah; Tria Wahyuningrum (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
The kindergarten years represent the "golden period" of early childhood, during which children experience rapid growth and development. Child development provides a critical foundation for future health and the quality of human resources. The family serves as the primary environment for a child's growth and development and plays a pivotal role in shaping the child's character. Families are primarily responsible for meeting children's basic needs, including developmental stimulation, care, and affection, all of which directly influence their physical, cognitive, language, social, and emotional development. However, many families still lack a comprehensive understanding of their role in providing optimal developmental stimulation, which may result in developmental delays that remain undetected during the early stages. This issue is particularly important in the context of community midwifery and maternal and child health services. This study aimed to analyze the relationship between the family environment and child development at Al Izzah Kindergarten, Mojokerto. A quantitative correlational research design was employed. The intended outputs of this study include an ISBN-registered book and a research article published in a SINTA-indexed journal. The findings showed that the majority of children experienced a positive family environment. Furthermore, the results of the Pre-Screening Questionnaire for Child Development (KPSP) indicated that almost all children demonstrated age-appropriate development. Data were analyzed using Fisher's Exact test. The statistical analysis revealed a significant relationship between the family environment and child development (p = 0.001, p < 0.05). The study concludes that the family environment plays a significant role in supporting child development at Al Izzah Kindergarten, Mojokerto. Therefore, families should provide age-appropriate developmental stimulation to promote optimal child development.